Service Quality of Government Bank in Rural Area of Uttarakhand (India) - Dr. Sanjeev Saxena; Mayank Jindal (International Journal of Engineering and Management Research, 2021)
We know that the approx and over 65% portion of India’s population resides in the rural areas of the country and therefore rural banking plays an important role in the Indian financial system. Remote areas usually have limited number of opportunities for survival and growth. The need for proper rural banking infrastructure cannot be overlooked in these distant remote regions especially in the wake of sustainable development of the country as a whole. Demand the higher agricultural technology, we need in turn higher uses of funds and that can only be fulfilled through rural banking. Economic liberalization lead lot many firms, companies, and SMSE to rise and live up to the expectation of rural society. These stakeholders are working in a challenging situation in hard geographical zones and hence need proper banking support and financial inclusion. Just to justify the topic ‘Rural banking’ and that too in hard geographical sphere, we selected hard remote region of Uttarakhand for research and 100 samples have collected through structured interview schedule. The paper is designed to investigate customer satisfaction of public banks in the rural segment.